2010
DOI: 10.1093/annonc/mdq221
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-emergent hypertension and outcomes in patients with advanced non-small-cell lung cancer receiving chemotherapy with or without the vascular endothelial growth factor receptor inhibitor cediranib: NCIC Clinical Trials Group Study BR24

Abstract: In advanced NSCLC, HTN is frequent in patients receiving chemotherapy, with or without cediranib. The development of HTN was favorably prognostic in these patients, but not predictive of a differential outcome with cediranib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The incidence of hypertension reported for the different RTKIs shows considerable variation, and especially, high rates of hypertension in over 60% of patients have been reported for the RTKIs cediranib and lenvatinib. 20,21 The reported difference in the incidence of hypertension may be explained by the intensity of blockade of the VEGFR-2 induced by the different VSP inhibitors. Furthermore, blockade of additional tyrosine kinases by the different RTKIs may play a role in the development of hypertension either by contributing to or by antagonizing the rise in BP.…”
Section: Incidence Of Hypertension and Renal Injurymentioning
confidence: 99%
“…The incidence of hypertension reported for the different RTKIs shows considerable variation, and especially, high rates of hypertension in over 60% of patients have been reported for the RTKIs cediranib and lenvatinib. 20,21 The reported difference in the incidence of hypertension may be explained by the intensity of blockade of the VEGFR-2 induced by the different VSP inhibitors. Furthermore, blockade of additional tyrosine kinases by the different RTKIs may play a role in the development of hypertension either by contributing to or by antagonizing the rise in BP.…”
Section: Incidence Of Hypertension and Renal Injurymentioning
confidence: 99%
“…In a study using axitinib treatment for Japanese patients with MKC, Tomita et al (11) indicated that baseline proteinuria and soluble VEGFR-2 levels may be predictive factors of axitinib-induced proteinuria, which may also be a predictive factor of a good response to axitinib. With regard to HT, a study of the VEGFR-TKI, cediranib, for non-small cell lung cancer indicated that predictors of VEGFR-TKI-induced HT were as follows: Eastern Cooperative Oncology Group performance status 0; female; normal lactate dehydrogenase levels; and no prior peripheral vascular disease (12). A meta-analysis of sunitinib indicated a significantly higher incidence of sunitinib-induced HT in MKC compared with gastrointestinal stromal tumors (13).…”
Section: Discussionmentioning
confidence: 99%
“…Existing data indicate a possible predictive role for single nucleotide polymorphisms (SNPs) in the VEGF signaling pathway, as well as treatment-emergent hypertension, but the clinical importance of this remains to be evaluated [48]. However, another VEGF receptor inhibitor, cediranib, showed no predictive association for hypertension in the NCIC Clinical Trials Group study BR24 [49].…”
Section: Angiogenesis Inhibitionmentioning
confidence: 99%